Husaini M. Hasan on The Concept of Political Activism in The Social And Political Context of Aceh - Bustami; Elly Wanisyah Harahap (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article analyzes Aceh's political activism from a political and historical perspective. This research uses a qualitative methodology, which focuses on the role of Husaini M. Hasan in the Free Aceh Movement and his struggle for the implementation of Islamic law in Aceh. This article explains how Aceh has struggled to maintain its Islamic identity within the framework of the Unitary State of the Republic of Indonesia from colonial times to contemporary times. This research analyzes various documents and interviews to show how Aceh's desire to implement Islamic law is related to the desire for regional autonomy and national identity. Aceh's social and political identity was shaped by political activism and Islamic ideology, which also interacted with Indonesian national politics. This study found that the political initiative in Aceh was not an independent state, but special autonomy. This shows that understanding and dealing with problems related to social identity, politics, and Islamic law in Aceh requires a more holistic and contextual approach.